The impact of health events on individual labor market histories: the message from difference in differences with exact matching. L’impact des événements de santé sur la carrière professionnelle : une analyse fondée sur la méthode des doubles différences avec appariement exact - Duguet, Emmanuel; Le Clainche, Christine (Noisy-le-Grand, 2012)
"We studied the effect of health events (accidents and chronic diseases) on the occupation probabilities at the individual level, while accounting for both correlated individual and time effects. Using difference-in-differences with exact matching estimators, we found that health events have a strong impact on individual labor market histories. The workers affected by a health event have a stronger probability of entering inactivity and a lower probability of keeping their jobs. We also found that the less qualified workers, women, and workers with short term jobs are the most negatively affected by health events."